2018
DOI: 10.1364/oe.26.019627
|View full text |Cite
|
Sign up to set email alerts
|

Linearly chirped mid-infrared supercontinuum in all-normal-dispersion chalcogenide photonic crystal fibers

Abstract: We demonstrate all-normal dispersion supercontinuum generation in chalcogenide photonic crystal fibers pumped at 2070-2080 nm with a femtosecond fiber laser. At 2.9 kW peak power, the generated supercontinuum has a 3 dB bandwidth of 27.6 THz and -20 dB bandwidth of 75.5 THz. We experimentally investigated the supercontinuum evolution inside our sample fiber at various peak powers and fiber lengths and study the impact of fiber water absorption on the generated supercontinuum spectrum. Multiple tests with fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 29 publications
2
19
1
1
Order By: Relevance
“…By contrast, achieving fully coherent octave-spanning SC with high spectral flatness is possible when pumping waveguides with sub-picosecond pulses in a low all-normal dispersion (ANDi) regime. Such SCs were reported in various fiber platforms, including silica [8][9][10], silicate soft glass [11,12], chalcogenide [13][14][15][16] fibers. However, SC generation in the ANDi regime on a chip has been only achieved in a chalcogenide waveguide [17] without any discussion about the phase coherence properties across the SC spectrum.…”
mentioning
confidence: 79%
“…By contrast, achieving fully coherent octave-spanning SC with high spectral flatness is possible when pumping waveguides with sub-picosecond pulses in a low all-normal dispersion (ANDi) regime. Such SCs were reported in various fiber platforms, including silica [8][9][10], silicate soft glass [11,12], chalcogenide [13][14][15][16] fibers. However, SC generation in the ANDi regime on a chip has been only achieved in a chalcogenide waveguide [17] without any discussion about the phase coherence properties across the SC spectrum.…”
mentioning
confidence: 79%
“…In 2018, an octave-spanning SC, covering 1.124-2.4 μm, was generated in SOI ridge waveguides [38]. In order to avoid the inherent nonlinear loss encountered in silicon in the near infrared and achieve broader SC spectra, the research moved toward other platforms, such as silicon nitride [39], chalcogenide [40], silicon-germanium [41], indium gallium phosphide [42], and aluminum nitride [43]. In the context of SC generation, Guo et al [44] have reported a mid-infrared comb source from 2.5 μm to 4 μm in silicon nitride (Si 3 N 4 ) waveguides and, recently, a (400-2400)-nm supercontinuum source has been demonstrated in integrated lithium niobate waveguides [45].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a wide choice of ND segments becomes possible for high-quality pulse compression in the alternating structures. Of fundamental interest is that this newly discovered phase effect explains more rigorously why, in general, ND SCG has a near parabolic spectral profile found in various experiments in the last decade [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 92%